2022
DOI: 10.3389/fmed.2022.1020126
|View full text |Cite
|
Sign up to set email alerts
|

Patients with inflammatory bowel disease have a higher chance of developing periodontitis: A systematic review and meta-analysis

Abstract: Background and objectivePeriodontitis affects up to one billion people worldwide, and has been proven to be associated with several systemic inflammatory conditions. This study investigates the specific relationship between two multifactorial diseases: Inflammatory bowel disease (IBD) and periodontitis. To thoroughly explore this issue, we investigated separately whether IBD patients have a higher chance of developing periodontitis, and equally, whether patients with periodontitis have a higher chance of devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The oral cavity is one of the most vulnerable areas for extraintestinal manifestations of IBD, and numerous studies have found that patients with IBD have a higher risk of periodontitis than those without IBD (Papageorgiou et al, 2017;She et al, 2020;Zhang et al, 2021c;Abrol et al, 2022). In addition, the severity and extent of periodontitis suffered by patients with IBD was found to be greater, with patients having significantly higher mean probing depth, plaque index, calculus index, sulcus bleeding index, and attachment loss than patients with general periodontitis (Zhang et al, 2020;Nijakowski et al, 2021;Domokos et al, 2022). It has also been confirmed that patients with periodontitis have a significantly higher risk of developing IBD than healthy controls without periodontitis (Lin et al, 2018;Kang et al, 2020;Madsen et al, 2022).…”
Section: Prevalence and Comorbiditymentioning
confidence: 82%
“…The oral cavity is one of the most vulnerable areas for extraintestinal manifestations of IBD, and numerous studies have found that patients with IBD have a higher risk of periodontitis than those without IBD (Papageorgiou et al, 2017;She et al, 2020;Zhang et al, 2021c;Abrol et al, 2022). In addition, the severity and extent of periodontitis suffered by patients with IBD was found to be greater, with patients having significantly higher mean probing depth, plaque index, calculus index, sulcus bleeding index, and attachment loss than patients with general periodontitis (Zhang et al, 2020;Nijakowski et al, 2021;Domokos et al, 2022). It has also been confirmed that patients with periodontitis have a significantly higher risk of developing IBD than healthy controls without periodontitis (Lin et al, 2018;Kang et al, 2020;Madsen et al, 2022).…”
Section: Prevalence and Comorbiditymentioning
confidence: 82%
“…A close relationship between inflammatory diseases and periodontitis has been described in a recent systematic review and meta‐analysis 539 : Patients with inflammatory bowel disease, being a high‐risk population in dentistry, had a higher chance of developing periodontitis (OR = 2.65; ranged from OR = 2.22 in Crohn's disease patients to OR = 3.52 in ulcerative colitis patients). Moreover, periodontitis was a significant risk factor for the development of ulcerative colitis but not Crohn's disease 539 . Several hypotheses have been proposed to explain the relationship between RA and periodontal disease 540,541 .…”
Section: Host‐related Factors Altering Bone Metabolismmentioning
confidence: 83%
“…[536][537][538] This fact may be explained by the long-term use of disease-modifying anti-rheumatic drugs (DMARDs) that may improve the periodontal condition due to their host modulatory effect. 536 A close relationship between inflammatory diseases and periodontitis has been described in a recent systematic review and meta-analysis 539 : Patients with inflammatory bowel disease, being a high-risk population in dentistry, had a higher chance of developing periodontitis (OR = 2.65; ranged from OR = 2.22 in Crohn's disease patients to OR = 3.52 in ulcerative colitis patients). Moreover, periodontitis was a significant risk factor for the development of ulcerative colitis but not Crohn's disease.…”
Section: Otherimmunedisordersmentioning
confidence: 89%
See 1 more Smart Citation
“…Inflammatory bowel disease (IBD) affects-depending on the disease entity (i.e., ulcerative colitis [UC] or Crohn's disease [CD])-parts of or the entire gastrointestinal tract, and often has extra-intestinal manifestations (EIM) involving the joints, eyes, skin, and/or the oral cavity. Additionally, IBD is associated with oral conditions such as caries and periodontitis (see for reviews Agossa et al, 2017Agossa et al, , 2021Domokos et al, 2022;Lorenzo-Pouso et al, 2021;Nijakowski et al, 2021;Papageorgiou et al, 2017;She et al, 2020;Zhang et al, 2021). In a recent large-scale, questionnaire-based, case-control study in Denmark, the association between IBD and oral health was further investigated based on answers of over 1100 IBD patients and more than 3400 matched controls.…”
Section: Introductionmentioning
confidence: 99%